Reverse Engineering of Z-Axis Slideways of CNC Lathe Machine Okuma-Howa ACT 3 - Fairuz Nugroho, Ferdiansyah
The z-axis of lathe machine is the direction of carriage’s motion along the bed on lathe which is parallel to the spindle axis and the positive direction is away from the headstock. The ideal movement of components on z-axis only gives one degree of freedom. Thus, there is no deviation either in position, linear, or angular orientation in straight motion of z-axis. Geometric characteristics are specification that should be maintained in order to get accurate z-axis lathe direction movement. Stackup tolerance method is used to determine the best of variation of geometric tolerance. Therefore, performance requirement of lathe can be achieved. Based on ISO 13041-1:2004, there are two requirements for carriage movement in z-axis direction. These are parallelism between movement in z-axis direction toward the spindle rotation axis and angular deviation of the z-axis movement. Each of these requirements has tolerance limit value that should be achieved. In this research, the stackup tolerance analysis model used is worst-case model. The result of stackup tolerance calculation are optimized to get the best tolerance variation. The optimized tolerances are applied to technical drawings. This model can be used as a reference in designing CNC lathes made in Indonsesia.